Public Sentiment Analysis Towards the Implementation of 2024 Election Preparations Using the Maximum Entropy Method - Indra Ismawan, Indra Ismawan; Mustikasari, Mustikasari; Saputra, Wahyuddin (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2024)
The General Election Commission (KPU) and the Election Supervisory Agency (Bawaslu) are tasked with coordinating and overseeing elections throughout the territory of Indonesia. Nevertheless, elections are not without various disputes, including violations of ethical codes and administrative issues. General elections are an important way for the public to exercise their political participation rights. In the era of information technology, the public is increasingly active in expressing their opinions and sentiments through social media such as Twitter. Utilizing data from social media, the maximum entropy method is employed to classify opinions found in tweets based on entropy values. This research also aims to measure the accuracy level of the maximum entropy method in sentiment classification. From the results of this study, using approximately 1,400 data, an accuracy rate of 87.08% was obtained, which is quite good and highly feasible for further development to achieve better results